Cardiovascular risk score associations with frailty in men and women with or at risk for HIV. (1st February 2022) - Kuniholm, Mark H.; Vásquez, Elizabeth; Appleton, Allison A.; Kingsley, Lawrence; Palella, Frank J.; Budoff, Matthew; Michos, Erin D.; Fox, Ervin; Jones, Deborah; Adimora, Adaora A.; Ofotokun, Igho; D'souza, Gypsyamber; et al.
Abstract : Objective: To understand the relationship between cardiovascular disease (CVD) risk and frailty among men (MWH) and women living with HIV (WWH), or at risk for HIV. Design: We considered 10-year coronary heart disease and atherosclerotic CVD risk by Framingham risk score (FRS, 2001 National Cholesterol Education Program Adult Treatment Program III) and Pooled Cohort Equations (PCE, 2013 American College of Cardiology/American Heart Association) in relation to the Fried Frailty Phenotype (FFP) in the Multicenter AIDS Cohort Study (MACS) and Women's Interagency HIV Study (WIHS). Methods: FFP was ascertained in MACS from 2004 to 2019 and in WIHS from 2005 to 2006 and 2011–2019. FFP score at least three of five components defined frailty. Repeated measures logistic regression (both cohorts) and Cox proportional hazards regression (MACS) were performed, controlled for education, income, cholesterol medication and hepatitis C virus serostatus, and among MWH and WWH, CD4 + cell count/μl, antiretroviral therapy, and HIV viral load. Results: There were 5554 participants (1265 HIV seronegative/1396 MWH; 768 seronegative/1924 WWH) included. Among men, high-risk FRS was associated with increased risk of incident frailty among seronegative [adjusted hazard ratio (aHR)) = 2.12, 95% confidence interval (CI):1.22–3.69] and MWH (aHR = 2.19, 95% CI: 1.33–3.61). Similar associations were seen with high-risk PCE and incident frailty among SN (aHR = 1.88, 95% CI: 1.48–2.39) and MWH (aHR = 1.59, 95% CI: 1.26–2.00). Among women, high-risk PCE was associated with frailty in SN [adjusted odds ratio (aOR) = 1.43, 95% CI: 1.02–2.00] and WWH (aOR = 1.36, 95% CI: 1.08–1.71); however, high-risk FRS was not (seronegative: aOR = 1.03, 95% CI: 0.30–3.49; WWH: aOR = 0.86, 95% CI: 0.23–3.20). Conclusion: Higher CVD risk was associated with increased frailty regardless of HIV serostatus among men and women. These findings may inform clinical practices of screening for frailty. Abstract : Supplemental Digital Content is available in the text